Pengaruh Modal, Tenaga Kerja Dan Pelatihan Terhadap Nilai Produksi Dan Pendapatan Industri Pakaian Jadi Di Kota Denpasar - Kadek Kesya Dwiyani Putri; Putu Ayu Pramitha Purwanti (Public Service and Governance Journal, 2023)
This research was conducted with the aim of evaluating the influence of capital, labor, and training on the production value of the ready-made garment industry in Kota Denpasar, as well as the influence of capital, labor, training, and production value on the industry's income. The research sample consisted of 88 units of ready-made garment industry businesses in Kota Denpasar, and path analysis was used as the analytical method. The results of the analysis indicated that capital, labor, and training have a positive impact on the production value of the ready-made garment industry in Kota Denpasar. Additionally, capital, labor, training, and production value also have a positive influence on the industry's income. Another interesting finding is that the production value acts as a mediator between capital, labor, and training and the income of the ready-made garment industry in Kota Denpasar.